Banking regulation in China : the role of public and private sectors - Ping, He Wei; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Bank Regulation in China provides an in-depth analysis of the country's contemporary banking regulatory system, focusing on regulation of foreign banks and consumer financial protection.
Keywords: Banks and banking -- China; Banking law -- China; Banks and banking, Foreign -- Law and legislation -- China